Usage of Graphing Calculator Ti-83 Plus: motivation and achievement - Noraini Idris, (penerbit ukm, 2006)
As the goals of education begin to change to reflect new social and educational needs, teaching strategies also change, and so, consequently, do strategies for integrating technology into teaching and learning. The purpose of this study was to investigate the use of graphing calculator as a tool in enhancing learning of mathematics. In this study the researcher did not assign subjects randomly to the treatment. Instead, a total sample of subjects in two intact classes was used, that is, one experimental class and one control class from form four. The study employed a quasi-experimental with pretest-posttest research design to determine the treatment effects. The experimental group used graphing calculator-based worksheets and each student has access to one graphing calculator during mathematics lesson. However, the control groups used textbook only and without graphing calculator. Both quantitative and qualitative methods were utilized to gather data. Quantitative data was collected using a pretest and posttest on mathematics achievement, mathematics attitude inventory, and questionnaire for students’ perception. Qualitative data on the hand was collected by means of observation and interview. The results of this study showed that students in the experimental group showed significantly greater improvement on mathematics achievement than students in the control group. Most of the students showed positive reactions towards the use of graphing calculator in their learning.